Women, peace and security : repositioning gender in peace agreements / Sahla Aroussi. - Aroussi, Sahla (Law and cosmopolitan values ;, 2015)
The adoption of Security Council resolution 1325 on women, peace and security in October 2000 marked the beginning of a global agenda on women in armed conflicts and post-conflict transition. Women, Peace and Security: Repositioning gender in peace agreements discusses the context and the content of this UN agenda and provides a systematic review of its implementation, over the last fifteen years, in peace agreements around the world. This book is timely, offering a valuable contribution to the literature on gender in armed conflicts, peace agreements, peace mediation, and transitional justice and is essential reading for practitioners and scholars working in this field. The study adopts an interdisciplinary approach to raise key theoretical and practical questions often overlooked by scholars working within the strict boundaries of the distinct disciplines. The book introduces a new dataset on peace agreements that provides important comprehensive evidence on the extent to which resolution 1325 and other subsequent resolutions on women, peace and security have impacted on peace agreements. Through the reflections of elite peacemakers, the book provides additional insights into the practice of peacemaking and the challenges of implementing the UN resolutions on women, peace and security on the ground. The findings of this book have important policy implications for governments, international organisations and NGOs who must refocus their efforts on bridging the gap between the theory and practice of gender sensitive peacemaking.'This exceptional study on the women, peace and security council resolutions is a significant contribution to the peace and security literature across multiple fields. Sahla Aroussi has produced a detailed, grounded and thoughtful assessment of the past fifteen years of United Nations Security Council resolutions grounded in thorough policy analysis and underpinned by a unique dataset. The work is particularly timely in light of the Global Study on the Women Peace and Security being undertaken in 2015. This thoughtful and scholarly analysis is grounded in a thorough and detailed empirical study, giving policy makers and academics substantial fodder for future work and reflection.Sahla Aroussi is to be commended for producing a work of immense depth and substance at such an important juncture in the contemporary history of the women, peace and security agenda. The book is a must read for policy makers, feminists and scholars working on these issues.'Fionnuala Ni Aolain, Professor of Law and Associate Director TJI, Ulster University & Professor of Law University of Minnesota'Dr Aroussi's The Women, Peace and Security Resolutions offers a unique insight into how, against certain odds, international standards trickle down and affect people's everyday lives, even in those very environments where that is least likely. This outstanding analysis is an inspiring account of the potential role of mediation and peace negotiation processes as platforms of norm socialization. Beyond its focus on gender, it is therefore most relevant for a wider audience interested in the nexus between international relations, international law and development.' Stef Vandeginste, Lecturer, Institute of Development Policy, University of Antwerp 'This is an outstanding book, which will be of immense value to researchers on conflict, conflict transformation, transitional justice and international law. ..a comprehensive and detailed account of international policy and practice, which will be an excellent resource for practitioners, scholars and researchers.' Carmel Roulston, Senior Lecturer in Politics, Ulster University